Risk of severe clinical events after sustained virological response following direct‐acting antiviral therapy in HIV and hepatitis C virus coinfected participants. Issue 9 (1st July 2021) - Chalouni, Mathieu; Wittkop, Linda; Bani‐Sadr, Firouzé; Lacombe, Karine; Esterle, Laure; Gilbert, Camille; Miailhes, Patrick; Zucman, David; Valantin, Marc Antoine; Brégigeon‐Ronot, Sylvie; Morlat, Philippe; Billaud, Eric; et al.
Abstract: Objectives: Sustained virological response (SVR) decreases the risk of hepatitis C virus (HCV)‐related events. Nevertheless, a substantial risk of events persists. We estimated incidences and identified factors associated with severe clinical events after SVR following treatment with a direct‐acting antiviral (DAA) in HIV/HCV‐coinfected patients. Methods: Participants from the ANRS CO13 HEPAVIH were included if they reached SVR. Incidence rates of overall mortality, liver‐related events, AIDS‐defining events, ischaemic events and non‐liver non‐AIDS‐defining cancers (NLNA) were estimated. Factors associated with the risk of those events were identified using Poisson models adjusted on age at SVR and sex. Results: In all, 775 participants were included. Incidence rates (95% confidence interval) of liver‐related events, overall mortality, AIDS‐defining events, ischaemic events and NLNA cancers per 1000 person‐years were 5.9 (3.3–10.3), 22.2 (16.8–29.5), 0.6 (0.1–4.5), 7.3 (4.4–12.2) and 13.7 (9.4–20.0), respectively. For all events, incidence rates were higher in cirrhotic than in non‐cirrhotic participants. Cirrhosis, liver stiffness and CD4 count were associated with liver‐related events. Factors associated with overall mortality were age, cirrhosis, liver stiffness and gamma‐glutamyl transferase (GGT). For ischaemic events and NLNA cancers, associated factors were total cholesterol and CD4 count, respectively. Conclusions: After SVR following a DAA treatment, liver‐related and AIDS‐defining events were observed less frequently than NLNA cancers. Severity of liver disease was associated with the risk of liver‐related events and of overall mortality but not with ischaemic events and NLNA cancers. Factors reflecting HIV infection were associated with NLNA cancers and liver‐related events.